Evaluation of neonatal admission to neonatal intensive care unit in a tertiary care hospital in Kashmir - Rashid, Rehana; Nazir, Muddasser; Sofi, Javid Ahmed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Neonatal period is the most unguarded period which influences the survival and overall wellbeing of a child. Many illnesses affecting the neonates lead to morbidities and mortality among them. According to 2015 Global health observatory (GHO) data, neonatal deaths constitute roughly 45% of all under five deaths. Worldwide, neonatal mortality rate has seen a steady decline by 47% between 1990 and 2015 from 36 to 19 per 1000 live birth. India contributes to nearly 25% of the mortality around the world. Methods: This descriptive retrospective study was carried out at LallaDed hospital, only tertiary care obstetrics and gynaecology hospital of Kashmir valley from August 2020 to January 2021. The study was conducted with records of the neonates who were admitted to NICU of this hospital during the above mentioned time period. The data regarding gestational age, sex, mode of delivery, birth weight, Apgar score at birth, indication for admission and outcome was recorded. Results: The total number of NICU admission during this time period was 252. The mode of delivery was FTVD in 144 (57.1%) and LSCS in 108 (42.9%). The number of preterm babies was 175 (69.4%) and number of term babies was 77 (30.6%). Among the admitted neonates, 141 (56%) were male and 111 (44%) were female babies. The birth Apgar score 0 minutes was 8 in 24, 7 in 75, 6 in 130 and 4 in 23 babies. Conclusions: This study identified RDS and MAS among the most common reasons for NICU admission. Early neonatal period is the major contributor to neonatal mortality which is influenced by birth weight and Apgar score. Understanding causes of neonatal mortality, education and training of medical and para medical staff and implementation of interventions regarding neonatal resuscitation will play major role in decreasing the neonatal NICU admission and mortality thereof.